The Evaluation of Performance Indicators Development: A Study on Indonesian Financial Transaction Report and Analysis Center (PPATK) - Dedy Kurniawan; Rusdi Akbar (Journal of Accounting and Investment, 2021)
Research aims: This research aims to evaluate the development of performance indicators using the performance blueprint analysis tools and know what factors are instrumental in the development of performance indicators for public organizations in Indonesia using Institutional Isomorphism point of view.Design/Methodology/Approach: The study comprised qualitative research undertaken at one public organization, the Indonesian Financial Transaction Reports and Analysis Center (PPATK) in Jakarta.Research findings: This study revealed that the PPATK business process was still not optimally aligned with the performance blueprint analysis tools. This study also uncovered eleven factors that play a role in the development of performance indicators: mindset, business process, comfort zone, technical competence, regulation, activity plan, process, drafting, management commitments, monitoring and evaluation, reward and punishment, and performance data management.Theoretical contribution/Originality: This study contributes to knowledge of the institutional isomorphism’s influence, primarily normative isomorphism at a public organization. Also, this research is the first research to use the performance blueprint more thoroughly, with six types of analysis.Practitioner/Policy implication: This study has implications for ministries/institutions and regulatory agencies to implement the performance blueprint in the development process of performance indicators.Research limitation/Implication: The limitations of this study are that the results of the performance blueprint analysis tools did not yet have the criteria as the basis for assessment of findings, and this research only employed a qualitative method; therefore, the resultant conclusions are still minimum.